INFORMATION TECNOLOGY IN EDUCATION AND TRAINING OF HEALTH PROFESSIONALS: AN INTEGRATIVE REVIEW - Carine Vendruscolo; Letícia de Lima Trindade; Marta Lenise do Prado; Juliana Homem da Luz; Grace Teresinha Marcon Dal Sasso; Alacoque Lorenzini Erdmann (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927465 Aim: to know the trends of scientific production on technologies in the field of information technology as a resource for the training and qualification of health professionals. Method: an integrative review that included scientific articles indexed in the Virtual health Library in 2007 at 2011. Results: 46 articles were identified that signal potentiality in the use of computers as a teaching resource, pointing out advantages and weaknesses, especially in training in healthcare. Considerations: the findings suggest the need for involvement and empowerment of teachers, changes in posture of academic and institutional investments, as well as monitoring the use of resources that involve the Information Technologies and Communication.